Experimental study of energy performance of grooved feed and grooved plasticating single screw extrusion processes in terms of SEC, theoretical maximum energy efficiency and relative energy efficiency. (1st March 2020) - Estrada, Omar; Ortiz, Juan Carlos; Hernández, Alexander; López, Iván; Chejne, Farid; del Pilar Noriega, María
Abstract: Experimental results of SEC, energy efficiency, backpressure and melt temperature in GFE and GPE as functions of PUT, rotational screw speed and die restriction are analyzed. For GFE, five screws are analyzed: two conventional, two barrier and one with a double-flighted feed zone. The polymer, motor drive, control system, die, screw diameter and length and temperature profile are the same. The differences in the results can be attributed to the PUT. Results show that the differences in the geometry of the GFE screws affect the extruder operational windows but do not significantly affect the SEC as a function of throughput. GPE shows higher productivity with a lower pressure requirement, SEC and melt temperature compared to GFE configurations. When the SEC of heaters and motor drive is compared between GPE and GFE technology, the behavior of the heater bands is similar but the motor drive energy is more efficiently used in GPE. A novel approach to the η m a x and η r in polymer extrusion is proposed, obtaining between 54.2% and 84.2% for maximum efficiency and 61.3%–86.2% for relative efficiency, depending on the PUT and the die restriction. Highlights: A novel approach to determine de theoretical maximum energy efficiency is proposed. An approach to evaluate the relative energy efficiency is proposed. GFE with five different screws and GPE are evaluated under de same conditions. The influence of rotational screw speed and die restriction is considered. Operational curve to integrate process control and energy efficiency is introduced.